Phase I Study Combining the Aurora Kinase A Inhibitor Alisertib with mFOLFOX in Gastrointestinal Cancer - Goff, Laura W. (Invest New Drugs, 2018)
Overexpression and cellular miss-localization of aurora kinase A (AURKA) in gastrointestinal cancers results in chromosomal instability, activation of multiple oncogenic pathways, and inhibition of pro-apoptotic signaling. Inhibition of AURKA causes mitotic delays, severe chromosome congression, and activation of p53/p73 leading to cell death. Our preclinical data showed cooperative activity with the AURKA inhibitor alisertib and platinum agents in cell lines and xenografts, and suggested an optimal treatment window. Therefore, this study was designed to determine the maximum-tolerated dose (MTD) of alisertib in combination with modified FOLFOX (mFOLFOX), as this is a standard platinum-based therapy for gastrointestinal cancers. Standard 3+3 dose escalation was used, where the starting dose of alisertib was 10 mg twice daily (Days 1–3), with leucovorin (400 mg/m(2)) and oxaliplatin (85 mg/m(2)) on Day 2 followed by continuous 46-hour 5-FU (2400 mg/m(2)) infusion on Days 2–4 in 14-day cycles. Fourteen patients with advanced gastrointestinal cancers were enrolled and two doses explored; two patients were not evaluable for dose-limiting toxicity (DLT) and replaced. Two patients experienced DLTs at 20 mg of alisertib (Grade 3 fatigue (n=2); Grade 3 nausea, vomiting, dehydration with hospitalization (n=1)). MTD was 10 mg alisertib with 85 mg/m(2) oxaliplatin and 2400 mg/m(2) 5-FU. Most frequent toxicities were nausea (57%), diarrhea, fatigue, neuropathy, and vomiting (43%), and anorexia and anemia (36%); most were Grade 1–2. One patient with colorectal cancer had a partial response of 12 evaluable patients, and four patients had stable disease. Alisertib in combination with mFOLFOX did not demonstrate unexpected side effects, but the regimen was only tolerable at the lowest dose investigated.